FACTORS AFFECTING STOCK EXCHANGE INVESTMENT IN KURDISTAN - Anwar, Kofand (Accounting Department,, 2017)
The purpose of this research is to examine the factors affecting stock exchange investment in Kurdistan and particularly in Erbil. Developing countries can also make use of these markets to develop their economy, though this process could be something new for some developing countries. The stock exchange investment is often the choice for businesses seeking lucrative investment deals. As the place where monetary transactions are made, investors usually take their chances in these markets based on studying expected revenues and risks accompanying said investments. Investors usually avoid high-revenue investments due to the great risks accompanying them and accept low-risk investments with little revenues. A quantitative method used to analyse the present research. The study was carried in Erbil. The researcher distributed 100 questionnaires, only 71 questionnaires were received and being completed properly. The researcher used single regression analysis in order to find factors affecting investment in stock exchange. The findings revealed that the highest value among all variables was supply & demand factor that influence stock, the second highest value was for economy factor then the third factor was competition factor and lastly the lowest value was for politic factor. According the findings, it seems that supply and demand play an essential role in investment in stock exchange in Kurdistan.